2016
DOI: 10.1016/j.urology.2016.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ureteroscopy Before Nephroureterectomy for Upper Tract Urothelial Carcinoma on Oncologic Outcomes

Abstract: Objective To compare the oncologic outcomes of patients with upper tract urothelial carcinoma (UTUC) undergoing nephroureterectomy (NU) with and without prior ureteroscopy (URS). Methods We reviewed records of all patients with no prior history of bladder cancer that underwent NU at our institution (n = 201). We compared patients who underwent URS prior to NU to patients who proceeded directly to NU based on imaging alone. After excluding patients undergoing URS with therapeutic intent, we used multivariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 18 publications
2
57
0
1
Order By: Relevance
“…Lee et al [17] divided patients who underwent preoperative URS into 2 groups, depending on the timing of URS, and they found that delay of RNU after URS significantly increased the risk for IVR. Sankin et al [9] also found the same relationship between time delay and risk for IVR. In contrast, Sung et al [11] revealed that the concurrent and delayed RNU after URS did not make any difference in the incidence of IVR or time to bladder recurrence, making the issue more complicated.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Lee et al [17] divided patients who underwent preoperative URS into 2 groups, depending on the timing of URS, and they found that delay of RNU after URS significantly increased the risk for IVR. Sankin et al [9] also found the same relationship between time delay and risk for IVR. In contrast, Sung et al [11] revealed that the concurrent and delayed RNU after URS did not make any difference in the incidence of IVR or time to bladder recurrence, making the issue more complicated.…”
Section: Discussionmentioning
confidence: 73%
“…All included studies in this review were retrospectively designed and inherently susceptible to selection bias, hence most studies included in this review reported that the baseline features were different between treatment arms and control arms [9, 10]. In addition, there are other possible differences that could be associated with the selection of diagnostic ureteroscopy and development of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 20 studies were excluded because of insufficient outcomes, and one was excluded due to potentially overlapping study populations. Finally, eight studies were included in the present meta-analysis [20][21][22][23][24][25][26][27]. Table 1 summarises the characteristics of the included studies [20][21][22][23][24][25][26][27].…”
Section: Data Analysis and Synthesismentioning
confidence: 99%
“…These patients with UTUC came from different countries or regions (USA, Japan, Austria, Canada, Germany, Italy, Chinese Taipei, France, Korea, and China) with a duration of follow-up of >12 months. Of the eight eligible studies, five studies [21][22][23][24]27] containing 2585 patients were conducted to investigate the impact of URS on the CSS of patients with UTUC after RNU, two studies [20,27] containing 297 patients investigated OS, two studies [22,24] containing 1780 patients investigated RFS, four studies [20,23,24,27] containing 1205 patients investigated MRS, and five studies [21,23,[25][26][27] containing 2099 patients investigated IRFS. Assessment of quality scores by the Newcastle-Ottawa scale showed that the scores of selected studies ranged from 7 to 9, which were considered adequate for the following meta-analysis ( Table 1).…”
Section: Data Analysis and Synthesismentioning
confidence: 99%